2023
DOI: 10.1590/0103-6440202305133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BlueM® against Streptococcus mutans biofilm and its virulence gene expression

Abstract: This study evaluated the antimicrobial capacity of BlueM® mouthwash against the bacterium Streptococcus mutans and its influence on gbpA gene expression as well as its cytotoxic effect on fibroblast cells. BlueM® showed antimicrobial activity, with MIC and MBC values of 0.005% and 0.01%, respectively. The MBIC was 6.25% for S. mutans. CFU count and confocal microscopy revealed significant effect of BlueM® on S. mutans biofilm pre-formed on dentin surfaces. Interestingly, the analysis of gbpA gene expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Furthermore, blue®m was found to be a safe alternative to CHX in reducing the total microbial colony counts in plaque samples obtained from gingivitis patients. The authors suggested that blue®m was equally effective in reducing the microbes when compared to CHX [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, blue®m was found to be a safe alternative to CHX in reducing the total microbial colony counts in plaque samples obtained from gingivitis patients. The authors suggested that blue®m was equally effective in reducing the microbes when compared to CHX [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the release of both oxygen and lactoferrin from blue®m agents may align with the five pillars of wound therapy: 1) increases cellular metabolism, 2) enhances collagen and epithelium synthesis, 3) facilitates the release of growth factors, 4) stimulates angiogenesis, and 5) impedes the growth of pathogenic bacteria and exerts bactericidal action, supported by the results of recent in animal and in vitro studies. Santos et al, showed the antimicrobial effectiveness of blue®m solution against S. mutans , its ability to modulate the expression of the gbpA gene and its low cytotoxicity on fibroblast cells ( Santos et al, 2023 ). Another in vitro study compared the effect of blue®m gel and 0.12 % CHX on Porphyromonas gingivalis , demonstrating that blue®m at a dose of 100 % and 75 % is similar to CHX ( Deliberador et al, 2020 ).…”
Section: Topical Oxygen Therapymentioning
confidence: 99%
“…For instance, Ntrouka et al [56] confirmed that oxygenating agent was significantly effective in controlling S. mutans biofilms. Currently, Santos et al [57] evaluated the antimicrobial capacity of blue®m formula against S. mutans and its virulence factors, e.g., gbpA gene expression. The study findings supported the preventive potential of BlueM oxygen agent on the control of oral biofilm related dental caries.…”
Section: Control Of Dental Cariesmentioning
confidence: 99%